2020
DOI: 10.1097/hs9.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Response Adapted Treatment Guidelines for Managing First Relapsed and Refractory Classical Hodgkin Lymphoma in Children and Young People. Recommendations from the EuroNet Pediatric Hodgkin Lymphoma Group

Abstract: The objective of this guideline is to aid clinicians in making individual salvage treatment plans for pediatric and adolescent patients with first relapse or refractory (R/R) classical Hodgkin lymphoma (cHL). While salvage with standard dose chemotherapy followed by high dose chemotherapy and autologous stem cell transplant is often considered the standard of care in adult practice, pediatric practice adopts a more individualized risk stratified and response adapted approach to salvage treatment with greater u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 91 publications
(192 reference statements)
2
74
0
3
Order By: Relevance
“…Our results influenced the recently published risk-and responseadapted treatment guidelines of the EuroNet-PHL group for managing a first relapse of classic HL in children and young adults (9). These guidelines recommend defining CMR in a first relapse as DS 1-3 or a qPET value of less than 1.3-similarly to first-line treatment.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our results influenced the recently published risk-and responseadapted treatment guidelines of the EuroNet-PHL group for managing a first relapse of classic HL in children and young adults (9). These guidelines recommend defining CMR in a first relapse as DS 1-3 or a qPET value of less than 1.3-similarly to first-line treatment.…”
Section: Discussionsupporting
confidence: 75%
“…PET is also used to guide treatment after relapse: patients with residual PET positivity after first-line salvage chemotherapy were switched to second-line salvage chemotherapy, and if they achieved CMR, they had a posttransplant outcome similar to that of patients achieving CMR with first-line salvage treatment (7). In the EuroNet-PHL-R1 trial, medium-risk children and adolescents achieving CMR after 2 cycles of secondline chemotherapy were deescalated to standard chemotherapy plus radiotherapy only, whereas inadequate responders received highdose chemotherapy and autologous stem cell transplantation (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…55 Relapsed or Refractory CHL Although the outcomes for pediatric HL are excellent, approximately 10% of patients with early-stage disease and up to 25% of patients with advanced-stage disease experience relapse. 8,56,57 For patients with relapsed or refractory disease, treatment options include standarddose chemotherapy (reinduction therapy), high-dose chemotherapy with ASCR, or novel approaches. 56 Reinduction regimens (see PHL-E 2 of 3, page 747) can be divided into 4 major categories.…”
Section: Follow-up After Completion Of Treatmentmentioning
confidence: 99%
“…It is considered as a curable pediatric cancer, since most patients are cured with first-line treatment and the 5-year survival rate is 90–95% [ 3 ]. Relapses occur in about 10–20% of patients, depending on disease stage [ 4 , 5 ]. Great attention is currently given to these subgroups of pediatric HL patients at risk of relapse, and several studies have reported candidate biomarkers predictive of relapse [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%